Millimetre Wave Communication with Spatial Division Multiplexing for 5G systems - et. al., Keshav N, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The point of this paper is to combination of spatial division multiplexing (SDMA) along with NOMA improves the performance of the system. This paper is done with multibeam forming for performance enhancement, Analog beam forming is done along with the digital beam forming to increase the spectral efficiency and also the user count increases so that we could able to achieve high throughput. In this paper the design problems of mm wave NOMA due to beamforming is focused so that achievable data rate is high. This is due to the number of RF chains. We analyses the demanding joint plan of the intertwined power distribution and client matching for mm Wave-SDMA. Some problems are talked about and a few arrangements are proposed in detail in mm Wave communications.